Editorial for the IJMS Special Issue on “Molecular Genetics of Autism and Intellectual Disability” - Hyung-Goo Kim (728597) (2023)
Autism spectrum disorder (ASD), a neurodevelopmental illness that affects children at an early age with a global prevalence of 1%, is diagnosed based on clinical features such as social impairment, repetitive behaviors, and restricted interests. ASD is genetically heterogeneous, and the genetic etiology of ASD remains unknown in 20–60% of autistic people. ASD subjects commonly have co-occurring comorbidities such as intellectual disability (ID), seizures, sleep problems, or digestive problems, which suggest more complex genetic etiologies. Exome sequencing and other next-generation sequencing (NGS) techniques have been successful in increasing the total number of known ASD genes. Other Information Published in: International Journal of Molecular Sciences License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/ijms241210394